Scope of Nanotechnology-based Radiation Therapy and Thermotherapy Methods in Cancer Treatment - K. Bakht, Mohamadreza; Sadeghi, Mahdi; Pourbaghi-Masouleh, Milad; Tenreiro, Claudio (Current Cancer Drug Targets, 2012)
The main aim of nanomedicine is to revolutionize the health care system and find effective approaches to fighting fatal diseases. Therapeutic beams, which are employed in radiation therapy, do not discriminate between normal and cancerous cells and must rely on targeting the radiation beams to specific cells. Interestingly, the application of nanoscale particles in radiation therapy has aimed to improve outcomes in radiation therapy by increasing toxicity in tumors and reducing it in normal tissues. This review focuses on approaches to nanotechnology-based cancer radiation therapy methods such as radionuclide therapy, photodynamic therapy, and neutron capture therapy. Moreover, we have investigated nanotechnology-based thermotherapy methods, including hyperthermia and thermoablation, as non-ionizing modalities of treatment using thermal radiation. The results strongly demonstrate that nanotechnology-based cancer radiation therapy and thermotherapy methods hold substantial potential to improve the efficacy of anticancer radiation and thermotherapy modalities.
Keywords: thermotherapy